2021
DOI: 10.3390/land10010043
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Explicit Evaluation and Driving Factor Identification of Land Use Conflict in Yangtze River Economic Belt

Abstract: Regional land use transitions driven by the adaptive reconciliation of existing land use conflict with socioeconomic development can lead to positive economic effects as well as new land use conflict. Although research on land use transition has progressed considerably, limited studies have explored the spatiotemporal dynamic pattern of land use conflict during the land use transition period. Previous evaluation approaches on land use conflict that mainly focus on status or potential conflict lack conflict int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 81 publications
0
15
0
2
Order By: Relevance
“…Previous studies had shown that SEFs were important driving factors of LUPs. Previous results on the effects of SEFs on the changes of LUPs were not always coincident due to the difference of spatial range in various study areas [28][29][30][31]. However, SEFs generally had both positive and negative effects on LUPs, which was less studied in previous research.…”
Section: Introductionmentioning
confidence: 79%
“…Previous studies had shown that SEFs were important driving factors of LUPs. Previous results on the effects of SEFs on the changes of LUPs were not always coincident due to the difference of spatial range in various study areas [28][29][30][31]. However, SEFs generally had both positive and negative effects on LUPs, which was less studied in previous research.…”
Section: Introductionmentioning
confidence: 79%
“…This novel application of participatory mapping captured spatial data across multiple catchments with varying land use and environmental characteristics by stakeholders from four key land and water management stakeholder groups. The heat maps of perceived conflict illustrated the complex combination of local and landscape-scale issues present in the catchments and identified the three main aspects of land use conflict-trade-offs between ecological, agricultural, and construction interests [66]. We were able to quantify how perceived conflicts differed between catchments and groups of stakeholders and used modelling of land cover types to predict conflict in the study catchments.…”
Section: Discussionmentioning
confidence: 99%
“…The second is the types of land use conflicts [55]. Many scholars mainly classify land use conflicts from different research perspectives, including conflict areas [56,57], conflict processes [58,59], conflict consequences [60][61][62], etc. The third is the identification of land use conflict [63].…”
Section: Deepening Understanding Of Space Conflictmentioning
confidence: 99%